2016
DOI: 10.2188/jea.je20150039
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Fine Particulate Matter Components and Daily Mortality in Nagoya, Japan

Abstract: BackgroundSeasonal variation and regional heterogeneity have been observed in the estimated effect of fine particulate matter (PM2.5) mass on mortality. Differences in the chemical compositions of PM2.5 may cause this variation. We investigated the association of the daily concentration of PM2.5 components with mortality in Nagoya, Japan.MethodsWe combined daily mortality counts for all residents aged 65 years and older with concentration data for PM2.5 mass and components in Nagoya from April 2003 to December… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
44
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 34 publications
2
44
2
Order By: Relevance
“…Cheng et al found a stronger association between PM 2.5 and pneumonia with septicemia ED visits during the warm season [4]. Ueda et al found that PM 2.5 mass correlated with increased all-cause mortality, especially in transitional seasons rather than in summer and winter [40]. Few studies have focused on the seasonal effects of air pollution on pediatric pneumonia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cheng et al found a stronger association between PM 2.5 and pneumonia with septicemia ED visits during the warm season [4]. Ueda et al found that PM 2.5 mass correlated with increased all-cause mortality, especially in transitional seasons rather than in summer and winter [40]. Few studies have focused on the seasonal effects of air pollution on pediatric pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…The present study revealed that ORs for NO 2 were higher during the warm days ( p = 0.011). One possible reason for this result is that variable concentrations of air pollutants and each PM component may relate to seasonal differences in human health [40, 41]. Seasonal variations may also result from different patterns of exposure to air pollutants.…”
Section: Discussionmentioning
confidence: 99%
“…Although more papers reported women as the susceptible gender to ambient air pollution, there are also studies indicated that the mortality of men was more sensitive to PM 2.5 [ 9 32 33 ]. These variations of the gender-based vulnerability to PM 2.5 across the studies may be due to different components of PMs as well as their proportions, since the components vary significantly across regions [ 34 35 ]. The haze is also a key risk for circulatory mortality, and most of the haze days in Shenyang occurred in winter [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Different PM 2.5 chemical compositions and health effects have gained increasing attention in Asian countries, where PM 2.5 concentrations are high—possibly driven by diverse pollution sources related to rapid urban development—and could affect large populations [11,12]. However, only a few single-city studies have been conducted in Asia, primarily due to the lack of PM 2.5 chemical component data [11,13,14,15,16,17]. The South Korean government established nationwide PM 2.5 chemical speciation networks in 2011 in order to identify major sources of PM 2.5 and monitor the level of chemical component concentrations [18].…”
Section: Introductionmentioning
confidence: 99%